New knowledge networks of small-scale farmers in Europe's periphery. (April 2017) - Sutherland, Lee-Ann; Madureira, Lívia; Dirimanova, Violeta; Bogusz, Malgorzata; Kania, Jozef; Vinohradnik, Krystyna; Creaney, Rachel; Duckett, Dominic; Koehnen, Timothy; Knierim, Andrea
Highlights: Small-scale farmers struggle to pay for independent advisory services. Small-scale farmers use social capital to access tacit knowledge for production. Small-scale farmers access knowledge from distant sources for diversification. Formal advisors were perceived to lack credible production knowledge. Small-scale farmers seek formal advice primarily to access subsidies. Abstract: In this paper we assess the types of knowledge networks utilised by small-scale farmers in four case studies (located in Bulgaria, Poland, Portugal, and the United Kingdom). We focus on knowledge acquired to inform three new activities being undertaken by study participants: agricultural production, subsidy access and regulatory compliance, and farm diversification (specifically agritourism). Findings demonstrate that the new knowledge networks are dominated by different forms of expertise: formal 'agricultural advisors' identified in the case studies primarily offer codified managerial knowledge through centralised networks, suggesting that state-funded services for small-scale farmers are largely embedded in traditional, linear models of knowledge transfer. Production and diversification knowledge is exchanged through 'distributed' and 'decentralised' networks, where a range of actors are involved across varying geographical distances. Findings highlight issues associated with the quality and independence of both 'free' and paid advice, as well as the importance of combining tacit and codified knowledge for credibility. In all four cases, we found that small-scale farmers utilise formal advisory services primarily for accessing subsidies (e.g. completing application forms), rather than acquiring production knowledge. The authors argue that by utilising the state funding allocated to advisory services for small-scale farmers primarily to enable these farmers to access subsidies, important opportunities for innovation by both advisors or farmers can be lost.